PERANCANGAN INTEGRASI OPEN DATA DENGAN MARKETPLACE DI KAWASAN TELUK TOMINI - Djamalu, Moh Suprianto; Koniyo, Moh Hidayat; Olii, Salahudin (Diffusion: Journal of Systems and Information Technology, 2023)
Currently there are many of organizations like government agencies, education institutions, the police and others taking advantage of internet services to share an open data. However, currently no one has been able to take the advantage of open data system which might be integrated into third party systems. For example is integrate the system with marketplace where the UMKM sellers are only specialized in certain areas. This research aims at designing the integration of open data system with marketplace system in area of Teluk Tomini using the prototype as development method. With the integrations of two systems, in which the UMKM sellers in the marketplace system which are only specialized in that area is no longer need to create a separate database for population as the needed data for verification, because the data already supplied by open data system. Likewise, organizations that registered in open data system can more easily monitor sales and budget fund that have been provided to UMKM sellers which are using the marketplace system for selling their products.